PENGGUNAAN APLIKASI SISTEM INFORMASI GEOGRAFIS DALAM PEMETAAN PERSEBARAN PEMBERI PELAYANAN KESEHATAN TINGKAT PERTAMA DALAM RANGKA PERSIAPAN PENYELENGGARAAN SISTEM JAMINAN SOSIAL NASIONAL DI KOTA DENPASAR - Luh Putu Eka Juliantini; Ketut Hari Mulyawan (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2013)
To achieve health coverage for all citizen of Indonesia, the government has launched a socialinsurance namely “Sistem Jaminan Sosial Nasional (SJSN)” which will be implemented in 2014.In the social insurance“Pemberi Pelayanan Kesehatan tingkat I, PPK I, have a central role as gatekeeper. This study purposed to gain information about the distribution of PPK I in the capital cityof Bali Province and assessed need level PPK I of Bali. The distribution and need level of PPK Ican be seen using Geographic Information System (GIS).This research was a cross-sectional descriptive study. Population and sample in this researchware all PPK I which registered in PT. Askes (Persero) and all of population in Denpasar.GIS analysis showed that PPK were not evenly distributed. PPK I distributed mostly in the centreof Denpasar. Based on cluster map can be seen that the highest clustered PPK I located in centreand West Denpasar area.PPK I need level map showed the mosted needed area was Pemogan village. PPK I need levelmap can be used by PT. Askes (Persero) to determine the PPK I need level in Denpasar city. It willbe easier for PT. Askes (Persero) to determine priority of distribution of PPK I.